CLASP2 is involved in the EMT and early progression after transurethral resection of the bladder tumor. Issue 1 (December 2017) - Zhu, Bisong; Qi, Lin; Liu, Sulai; Liu, Wentao; Ou, Zhenyu; Chen, Minfeng; Liu, Longfei; Zu, Xiongbing; Wang, Jun; Li, Yuan
Abstract Background Cytoplasmic linker-associated protein 2 (CLASP2) belongs to a family of microtubule plus-end tracking proteins that localizes to the distal ends of microtubules and regulate microtubule dynamics. We speculated that it might be involved in the epithelial-mesenchymal transition (EMT) and progression of bladder cancer (BC). Methods Western blotting and RT-PCR were used to detect the changes at protein and mRNA levels in BC cell lines. Cell proliferation, clonogenic formation, wound healing and chamber invasion assay were used to investigate the abilities of cellular proliferation, migration and invasion. The data of BC patients treated with transurethral resection of the bladder tumor (TURBT) was collected and analyzed. The levels of mRNA of CLASP2 and EMT-related markers in tumor and urine samples were tested by RT-PCR. Results Expressions of CLASP2 varied in four BC cell lines. Manipulation of CLASP2 expression changed EMT-related markers. CLASP2 could promote proliferation, migration and invasion in BC cell lines. The combination (CLASP2 + E-cadherin mRNA in urine) could better discriminate the patients with or without 2-years progression compared with tumor grade after TURBT. Conclusion CLASP2 is involved in the EMT and progression of bladder urothelial cancer. Simultaneous urine-based detection of CLASP2 and E-cadherin mRNA can efficiently discriminate patients with or without 2-years progression after TURBT.